Harnessing chondroitin sulphate in composite scaffolds to direct progenitor and stem cell function for tissue repair. (21st March 2018) - Farrugia, B. L.; Lord, M. S.; Whitelock, J. M.; Melrose, J.
Abstract : This review details the inclusion of chondroitin sulphate in bioscaffolds for superior functional properties in tissue regenerative applications. Abstract : The development of bioscaffolds that incorporate chondroitin sulphate (CS) and their applications with progenitor and stem cells in cartilage, bone, cornea, skin, and neural repair are reviewed. CS is a heterogeneous structure due to the organisation of multiple CS disaccharide sulphation motifs, giving rise to a vast range of CS chain structures, and hence the wide range of biological activity. The incorporation of this biological molecule represents a significant advance in bioscaffold design and performance in tissue repair strategies. The intrinsic stem-cell directive properties of CS are covered in the context of tissue development, and the differing CS disaccharide motifs, referred to as the 'glyco-code'. These structural motifs contribute to stem cell proliferation and differentiation in the scaffold environment and improve outcomes in terms of tissue repair or regeneration worthy of future research.